In Determinants Of Patient Satisfaction Health Care - Sabarinath R; Dr. K Maharajan (Revista Electronica de Veterinaria, 2024)
Understanding patient needs, issues and experiences is crucial for healthcare providers and measuring patient satisfaction enables you to do this. It provides invaluable insights that can drive improvements, foster patient loyalty, and enhance the overall quality of care. Review of related literature shows patients satisfaction is determined by certain active and passive factors. Present study is a conceptual analysis on the determinants of patient satisfaction. The study tries to find out the major factors that determine the satisfaction level of the patients. Major factor extends from Interpersonal care to outcome of care.